Seruan Kebangkitan Islam dalam Majalah Pengasuh: Tinjauan Terhadap Tulisan Tok Kenali dan Zaaba. - Abdul Hamid, Faisal @ Ahmad Faisal (Jurnal Usuluddin, 2010)
During the early part of the 20th century, the religious magazines were published were primarily interest incurred. The contents of these magazines, which discussed a variety of issues, enabled them to act as a double edged sword; in that they both helped to raise the fighting spirits of the Malays and also foster good values based on Islam. One of the oldest and most influential magazines during these times was the Pengasuh magazine. During its long existence, which is nearing 92 years, many written works which have influenced the spirits of the Malay can be reviewed. In this research paper, we will showcase several articles written by Za’aba and Tok Kenali which were published in the Pengasuh, so that the intellectual views contained in them may be shared for the good of the present generation. Some of these issues, which are also currently being discussed and debated, are the racial awareness and values of the Malays, and the relationship between knowledge and economy in developing a nation of honour and distinction. Apart from that, Za’ba also once said “the glory of a nation is in its language”. Therefore, it is these themes that will be discussed in this research paper.